2011
DOI: 10.1007/s00127-011-0419-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of the PICMIN (picture of mental illness in newspapers): instrument to assess mental illness stigma in print media

Abstract: PICMIN instrument allows comparison among countries and different studies over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
(60 reference statements)
0
9
1
2
Order By: Relevance
“…The proportion of stories coded as stigmatizing (46.0%) was higher than previous work by Rukavina et al, (2012), who found rates from 28.8% to 38.6% using the same coding protocol (PICMIN) in Croatian, Czech, and Slovak media samples. Five story features independently predicted higher levels of stigma.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…The proportion of stories coded as stigmatizing (46.0%) was higher than previous work by Rukavina et al, (2012), who found rates from 28.8% to 38.6% using the same coding protocol (PICMIN) in Croatian, Czech, and Slovak media samples. Five story features independently predicted higher levels of stigma.…”
Section: Discussioncontrasting
confidence: 75%
“…A manual was developed that enabled each story to be coded on multiple features: (1) word count, (2) news outlet, (3) referenced country or countries, (4) metaphoric versus non-metaphoric use of "schizophrenia" (using criteria developed by Magliano, Read, & Marassi, 2011), (5) presence of any reference to crime, (6) presence of any reference to violence (coded for homicide or attempt, suicide or attempt, assault, other violence, or none), (7) whether a "schizophrenic" person was identified as a victim or perpetrator of violence, (8) the gender of any person identified as "schizophrenic", (9) the age of any person identified as schizophrenic (coded as older adult [30+], young adult [18][19][20][21][22][23][24][25][26][27][28][29], adolescent [13][14][15][16][17] or child [<13]), (10) whether illicit drugs or alcohol use was mentioned, and (11) whether the story as a whole was stigmatizing, neutral, mixed, or destigmatizing (coding instructions from Rukavina et al, 2012).…”
Section: Coding Manualmentioning
confidence: 99%
See 2 more Smart Citations
“…Media represent an important means to disseminate information about diseases, treatments, and available resources. However, not all images displayed by the media are correct, often inducing erroneous and stigmal beliefs in the community about people with certain diseases and influencing the illness representation of the person living with the disease (Collin & Hughes, 2011;Drazic & Caltabiano, 2012;Holland, 2012;Rukavina et al, 2012). In the case of FAP, as an hereditary disease with a strong psychosocial impact, it is important to perform an analysis of the news published by the association representing the interests of the persons living with it.…”
Section: Literature Reviewmentioning
confidence: 99%